Procedural justice and achieving organizational goal: A study of Academic Staff of Bauchi State University Gadau - Hassan, Abubakar Idris; Mansur, Mohammed Wali (Kashere Journal of Politics and International Relations, 2023)
Gobally organizations are created to achieve predetermined objectives and in order to achieve these objectives there is a need to assemble human and material resources. Universities are organizations that assume the role of training and producing competent graduates. Like any other organization, Bauchi State University Gadau has the problems of equal treatment of its employees to work productively and qualitatively towards the achievements of their set objectives; hence there is need for procedural justice. This study was designed to assess impact of procedural justice on academic staff performance of Bauchi State using organizational support theory and expectancy theory. Survey research was adopted for this research; data was collected using the survey questionnaire instrument and analyzed using multiple regressions on SPSS version 21. The result of study shows that procedural justice has an impact on academic staff performance towards achieving organizational goal. It was therefore recommended that Bauchi State University Gadau should give more emphasis on procedural justice so as to boost the performance of staff towards achieving predetermined goals and objectives and thus gives employees a sense of belonging and commitment to duty to achieve productivity.